2016
DOI: 10.1002/hed.24445
|View full text |Cite
|
Sign up to set email alerts
|

Poor prognosis in human papillomavirus–positive oropharyngeal squamous cell carcinomas that overexpress hypoxia inducible factor‐1α

Abstract: HIF-1α overexpression is associated with worse OS and characterized a subgroup of patients with HPV-positive oropharyngeal SCC with poor prognosis. Possibly, patients with HIF-1α overexpressing HPV-positive tumors should not be eligible for treatment dose deescalation. © 2016 Wiley Periodicals, Inc. Head Neck 38: 1338-1346, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…Meanwhile, Ayala and colleagues [13] also identified GLUT-1 as an indicator for poor overall survival ( P  = 0.006) in their study. Swartz et al [15] also found significantly prognostic role of GLUT-1 in OSCC by univariate overall survival analysis ( P  = 0.026). In contrast, other studies did not find any significant association between GLUT-1 and outcome of OSCC patients.…”
Section: Introductionmentioning
confidence: 89%
“…Meanwhile, Ayala and colleagues [13] also identified GLUT-1 as an indicator for poor overall survival ( P  = 0.006) in their study. Swartz et al [15] also found significantly prognostic role of GLUT-1 in OSCC by univariate overall survival analysis ( P  = 0.026). In contrast, other studies did not find any significant association between GLUT-1 and outcome of OSCC patients.…”
Section: Introductionmentioning
confidence: 89%
“…HNSCC tumours are also characterized by hypoxia, with roughly similar levels of hypoxia in HPV-positive and HPV-negative tumours of the same stage 119 . High levels of hypoxia in tumours portend a poor prognosis and resistance to radiation therapy [120][121][122][123][124] . Hypoxia induces the expression of HIF1α, a subunit of the transcription factor HIF1, which drives expression of a range of genes encoding proteins that promote angiogenesis (VEGF) and degradation of ECM (MMPs).…”
Section: Tumour Microenvironmentmentioning
confidence: 99%
“…HIF-1α overexpression has been associated with poor prognosis, advanced disease, an aggressive cancer phenotype and poor response to radiotherapy in a number of malignancies, including HNSCC. 46 There is clear clinical utility to using hypoxia-related proteins such as CAIX or HIF-1α as surrogate markers of tumour hypoxia as they can be easily detected in tissue samples, have low assay costs, offer the potential of marker co-detection and the possibility of repeatedly detecting and monitoring biomarkers when samples are available. Extrinsic markers of hypoxia such as EF5 and pimonidazole are non-physiologic substances that are injected into the body where they accumulate under hypoxic conditions as a result of chemical reduction and covalent binding to macromolecules.…”
Section: Hypoxia Detection and Patient Stratificationmentioning
confidence: 99%